Anaerobic Metabolism of Cyclohex-1-Ene-1-Carboxylate, a Proposed Intermediate of Benzoate Degradation, by Rhodopseudomonas palustris - Perrotta, Joseph A. (1994)
Anaerobic benzoate degradation by the phototrophic bacterium Rhodopseudomonas palustris has been proposed to proceed via aromatic ring reduction reactions leading to cyclohex-1-ene-1-carboxyl-coenzyme A (CoA) formation. The alicyclic product is then proposed to undergo three β-oxidation-like modifications resulting in ring cleavage. Illuminated suspensions of benzoate-grown cells converted [7-(14)C]cyclohex-1-ene-1-carboxylate to intermediates that comigrated with cyclohex-1-ene-1-carboxyl-CoA, 2-hydroxycyclohexanecar-boxyl-CoA, 2-ketocyclohexanecarboxyl-CoA, and pimelyl-CoA by thin-layer chromatography. This set of intermediates was also formed by cells grown anaerobically or aerobically on cyclohex-1-ene-1-carboxylate, indicating that benzoate-grown and cyclohex-1-ene-1-carboxylate-grown cells degrade this alicyclic acid by the same catabolic route. Four enzymatic activities proposed to be required for conversion of cyclohex-1-ene-1-carboxylate to pimelyl-CoA were detected at 3- to 10-fold-higher levels in benzoate-grown cells than in succinate-grown cells. These were cyclohex-1-ene-1-carboxylate-CoA ligase, cyclohex-1-ene-1-carboxyl-CoA hydratase, 2-hydroxycyclohexanecarboxyl-CoA dehydrogenase, and 2-ketocyclohexanecarboxyl-CoA hydrolase (ring cleaving). Pimelyl-CoA was identified in hydrolase reaction mixtures as the product of alicyclic ring cleavage. The results provide a first demonstration of an alicyclic ring cleavage activity.